2014
DOI: 10.1039/c4cc02768j
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light-induced direct C(sp3)–H difluromethylation of tetrahydroisoquinolines with the in situ generated difluoroenolates

Abstract: An effective approach to C1-difluoromethylated tetrahydroisoquinoline derivatives has been developed through C-H functionalization of tertiary amines by visible-light photoredox catalysis. This method uses stable, easily obtained α,α-difluorinated gem-diol as the CF2 source. The corresponding products were obtained in moderate to high yields at ambient temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 49 publications
1
44
0
Order By: Relevance
“…In 2014, Zhu and co‐workers achieved the visible light‐induced difluoromethylation of tetrahydroisoquinolines with β,β‐difluorinated gem ‐diols as CF 2 source . As a continuation of their interest in visible light‐promoted C−H bond activation and in consideration of the importance of fluoro‐containing organic compounds, these authors reported the monofluoromethylation of tetrahydroisoquinolines with easily‐prepared trifluoromethyl β‐fluorinated gem ‐diols as CF source (Scheme ) …”
Section: C(sp3)−h Bond Functionalizationmentioning
confidence: 99%
“…In 2014, Zhu and co‐workers achieved the visible light‐induced difluoromethylation of tetrahydroisoquinolines with β,β‐difluorinated gem ‐diols as CF 2 source . As a continuation of their interest in visible light‐promoted C−H bond activation and in consideration of the importance of fluoro‐containing organic compounds, these authors reported the monofluoromethylation of tetrahydroisoquinolines with easily‐prepared trifluoromethyl β‐fluorinated gem ‐diols as CF source (Scheme ) …”
Section: C(sp3)−h Bond Functionalizationmentioning
confidence: 99%
“…9 In 2011, we demonstrated that difluoroenolates could be generated by the mild release of trifluoroacetate from pentafluoro- gem -diols using LiBr and Et 3 N. 12 The difluoroenolates react well with aldehydes, 12 imines, 13 and electrophilic halogenation reagents 14 (Figure 1). Subsequent innovations mediated by the release of trifluoroacetate include catalytic asymmetric aldol reactions, 15 integration with light-induced photoredox catalysis, 16 and stereoselective additions to chiral N -sulfinyl imines. 17 Indeed, the major advantage of using trifluoroacetate release is that it is quite mild yet compatible with many types of reagents.…”
mentioning
confidence: 99%
“…The same group52b has also reported similar reactions with difluoro enolate precursors 20 (Scheme ).…”
Section: Reactions Of Free Fluoro Enolates Generated In Situmentioning
confidence: 77%